Question:

If a tangent to the hyperbola \( x^2 - \frac{y^2}{3} = 1 \) is also a tangent to the parabola \( y^2 = 8x \), then the equation of such tangent with the positive slope is: 

Show Hint

To find a common tangent between a hyperbola and a parabola, use the standard tangent equations of both conic sections and equate them. Solve for the slope \( m \), and then substitute to get the required tangent equation.
Updated On: Mar 25, 2025
  • \( y - x - \frac{1}{2} = 0 \)
  • \( y - 2x - 1 = 0 \)
  • \( 2y - 4x - 1 = 0 \)
  • \( y - x - 1 = 0 \)
Hide Solution
collegedunia
Verified By Collegedunia

The Correct Option is B

Solution and Explanation

Step 1: Equation of the Tangent to the Hyperbola 
The equation of the given hyperbola is: \[ x^2 - \frac{y^2}{3} = 1. \] For a hyperbola of the form \( \frac{x^2}{a^2} - \frac{y^2}{b^2} = 1 \), the equation of the tangent at any point can be written as: \[ y = mx \pm \sqrt{a^2 m^2 - b^2}. \] Here, comparing with the standard form, we have \( a^2 = 1 \) and \( b^2 = 3 \). So, the equation of the tangent is: \[ y = mx \pm \sqrt{m^2 - 3}. \] 
Step 2: Tangent to the Parabola 
The equation of the given parabola is: \[ y^2 = 8x. \] For a parabola of the form \( y^2 = 4ax \), the equation of the tangent with slope \( m \) is given by: \[ y = mx + \frac{2}{m}. \] 
Step 3: Condition for Common Tangent 
Since the same line must be a tangent to both the hyperbola and the parabola, we equate the two forms: \[ mx \pm \sqrt{m^2 - 3} = mx + \frac{2}{m}. \] Comparing, we get: \[ \pm \sqrt{m^2 - 3} = \frac{2}{m}. \] Squaring both sides: \[ m^2 - 3 = \frac{4}{m^2}. \] Multiplying throughout by \( m^2 \): \[ m^4 - 3m^2 = 4. \] Rearranging: \[ m^4 - 3m^2 - 4 = 0. \] 
Step 4: Solving for \( m \) 
Let \( x = m^2 \), then the equation becomes: \[ x^2 - 3x - 4 = 0. \] Factoring: \[ (x - 4)(x + 1) = 0. \] Since \( x = m^2 \) must be positive, we take: \[ m^2 = 4 \Rightarrow m = \pm 2. \] 
Step 5: Finding the Tangent Equation 
Using \( m = 2 \) in the tangent equation of the parabola: \[ y = 2x + \frac{2}{2}. \] \[ y = 2x + 1. \] Rearranging: \[ y - 2x - 1 = 0. \] 
Final Answer: \( \boxed{y - 2x - 1 = 0} \)

Was this answer helpful?
0
0

Top Questions on Conic sections

View More Questions